PERSEPSI TERHADAP PELAYANAN RUMAH KOST DI KELURAHAN GEBANG REJO (PERCEPTION BOARDING HOUSE SERVICES IN VILLAGE GEBANGREJO) - Tabita R Matana (Ekomen, 2014)
The purpose of this study was to determine the perceptions of residents of the boarding house to boarding house services in the Village Gebangrejo Poso. The experiment was conducted in the village of Aru Poso Gebangrejo Jln.Pulau using primary data and secondary data. Data were collected through interviews and questionnaires. The population in this study were all residents of the Village boarding Gebangrejo totaling 35 people and all were sampled in the study.Data analysis using qualitative descriptive statistical analysis techniques. The result showed that (42.86% - 28.57%) to the perception of residents boarding house boarding Village Gebangrejo Poso excellent boarding house residents also expressed the services provided at the boarding house is quite satisfactory and excellent.Key words : Perceptions, Services, Boarding House